Impact of a revised postoperative care plan on pain and recovery trajectory following pediatric tonsillectomy. Issue 7 (18th April 2021) - Lagrange, Claudia; Jepp, Catherine; Slevin, Lliana; Drake‐Brockman, Thomas F. E.; Bumbak, Paul; Herbert, Haley; von Ungern‐Sternberg, Britta S.; Sommerfield, David
Abstract: Background: A previous cohort of adenotonsillectomy patients at our institution demonstrated moderate‐severe post‐tonsillectomy pain scores lasting a median (range) duration of 6 (0–23) days and postdischarge nausea and vomiting affecting 8% of children on day 1 following surgery. In this subsequent cohort, we evaluate the impact of changes to our discharge medication and parental education on post‐tonsillectomy pain and recovery profile. Methods: In this follow‐on, prospective observational cohort study, all patients undergoing tonsillectomy at our institution during the study period were discharged with standardized analgesia. Parents received a revised education package and a medication diary which were not provided to the previous cohort. Pain scores, rates of nausea and vomiting, medication usage and unplanned representation rates were collected by telephone from parents. Results: Sixty‐nine patients were recruited. Moderate‐severe pain lasted a median (range) of 5 (0–12) days. Twenty‐nine (42%) had pain scores ≥4/10 beyond postoperative day 7. By postoperative day 5, only 37 (53%) parents continued to administer regular analgesia. The median number of oxycodone doses used was 5 (0–22), and only 28 (41%) parents had disposed of leftover oxycodone within 1 month of surgery. Twenty‐four (35%) patients experienced nausea or vomiting postdischarge. The median (range) time for return to normal activities was 6 (0–14) days. Thirty‐two/sixty‐nine (46%) patients had unplanned medical representations. Most occurred between postoperative day 5 and 7. Pain contributed to 16 (35%) representations. Conclusions: Despite extensive changes to our discharge protocols parents continued to report a prolonged period of pain, post operative nausea and vomiting, and behavioral changes. Further work is required to examine barriers to compliance with simple analgesia and education in appropriate methods of opioid disposal.